Total colonic aganglionosis and cleft palate in a newborn with Janus-cysteine 618 mutation of RET proto-oncogene: a case report - Ingrid Anne Mandy Schierz; Marcello Cimador; Mario Giuffrè; Claudia Maria Aiello; Vincenzo Antona; Giovanni Corsello; Ettore Piro (Italian Journal of Pediatrics, 2020)
Abstract Background Hirschsprung disease, the most important congenital colonic dysmotility in children results from neural crest migration, differentiation, proliferation, or apoptosis defects where the rearranged during transfection (RET)-Protooncogene pathway has a central role. Although palatal and retinal anomalies in the context of chromosomopathies and some mono−/oligogenic syndromes are reported associated with Hirschsprung disease the role of inactivating RET mutations in these cases is not clarified. Case presentation We report on a dysmorphic newborn with cleft palate and palatal synechia, who showed intestinal obstruction after 24 h of life. Transient ileostomy and surgical biopsies were performed to diagnose aganglionosis of the colon and last ileal loop. No chromosomal anomalies or copy number variations were found. We identified a paternal heterozygous germline mutation c.1852 T > C, which results in the substitution of cysteine by arginine in the RET-receptor tyrosine kinase (p.C618R mutation). There was no family history of Hirschsprung disease, but the father underwent surgery for medullary thyroid carcinoma and was affected by retinal dystrophy. Conclusions The occurrence of Hirschsprung disease and carcinoma shows how a single mutation may be responsible for adverse effects: gain and loss of function of the same receptor. Furthermore, it would be interesting to study its dual role in face and retina embryology, and to extend targeted investigations of RET hotspots in these developmental abnormalities to facilitate counselling, follow-up, and tumor prevention. Complex surgical procedures and genetic testing as well as socio-economic impact are a challenge for familiar compliance.